Oxytocin Massage and Infant Massage on the Smooth Flow of Breast Milk - Purwandari, Atik; Korompis, Martha; Tuju, Sjenny Olga; Wahyuni, Wahyuni; Amdadi, Zulaeha A (Sarana Ilmu Indonesia (salnesia), 2024)
The global infant mortality rate remains a cause for concern, with 2.6 million babies worldwide not surviving beyond one month, and one million succumbing at birth, as reported by the United Nations Children's Fund (UNICEF). This study, conducted in North Minahasa district, seeks to address this issue by analyzing the effectiveness of Oxytocin Massage and Baby Massage, coupled with family support, in promoting the smooth production of breast milk. Employing a pre-experimental method with a one-group pre-and-post-test design, the research investigates the impact of Oxytocin Massage and Baby Massage on breastfeeding mothers and the subsequent release of breast milk. The findings, analyzed using Paired T Test, reveal a significant effect of both massages on breast milk production, with a p-value of 0,00. Oxytocin massage proves effective in facilitating breast milk release, as evidenced by the observed reduction in breast tension before breastfeeding (pre 23%, post 93,33%) and an increase in breast milk leakage (pre 23,3%, post 93,3%). Similarly, baby massage demonstrates effectiveness in promoting smooth breast milk release, reflected in increased breastfeeding frequency (pre 43,3%, post 66,7%), higher urination frequency (pre 40%, post 56,7%), and improved post-feeding sleep quality (pre 43,3%, post 96,7%). The study underscores the role of family support in optimizing breast milk flow, advocating for the implementation of Oxytocin Massage for breastfeeding mothers and Baby Massage within the household. This approach holds promise in addressing global infant mortality concerns by fostering healthier breastfeeding practices through accessible and family-centered interventions.